2021
DOI: 10.1016/j.eneco.2021.105446
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Zones in Australia's National Electricity Market

Abstract: Australia's National Electricity Market operates in one of the world's longest and stringiest transmission networks. The 2016-2020 investment supercycle, in which 13,000 MW of renewables were committed, is slowly revealing the limits of network hosting capacity for renewable plant. In this article, side-effects arising from the supercycle are analysed. The majority sources of renewable investment failure relate to deteriorating system strength, viz. associated connection lags, remediation and curtailment costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 76 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Further entry is likely to exacerbate curtailment until reinforcement arrives. Simshauser (2021) gives graphic evidence that poor foresight of future constraints (in this case, taking the form of increasing transmission loss factors) can lead to inefficient location decisions and financially costly outcomes that will feed back into future RESS auction bids.…”
Section: Discussionmentioning
confidence: 99%
“…Further entry is likely to exacerbate curtailment until reinforcement arrives. Simshauser (2021) gives graphic evidence that poor foresight of future constraints (in this case, taking the form of increasing transmission loss factors) can lead to inefficient location decisions and financially costly outcomes that will feed back into future RESS auction bids.…”
Section: Discussionmentioning
confidence: 99%
“…Apergis et al (2020) showed that power prices could fluctuate immensely to levels much higher than the long-term price, implying that Australian power market participants must possess sound risk management when transacting in the market. Third, according to Simshauser (2021), the world's longest transmission network is the Australian power market.…”
Section: Introductionmentioning
confidence: 99%
“…Tasmania joined the NEM in May 2005, while the Snowy region was abolished as a separate region in July 2008. There have been many studies of the Australian NEM (Bateson and Swan, 1989;Swan, 1990;Kim, 1997;Brennan and Melanie, 1998;Worthington et al, 2005; Contagions in power markets Reedman et al, 2006;Higgs and Worthington, 2008;Becker et al, 2007;Higgs, 2009;Thomas et al, 2011;Apergis and Lau, 2015;Apergis et al 2017aApergis et al , b, 2020Mishra and Smyth, 2017;Bell et al, 2017;Handika and Khudri, 2018;Smith and Shively, 2018;Han et al, 2020;Yan and Tr€ uck, 2020;Simshauser, 2021). However, none has examined contagions in the Australian interconnected power markets.…”
Section: Introductionmentioning
confidence: 99%